2023
DOI: 10.1021/acsnano.3c06599
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Toxicity of Boron Nitride Nanomaterials Is Aspect Ratio Dependent

Luis Augusto Visani de Luna,
Thomas Loret,
Yilin He
et al.

Abstract: Boron nitride (BN) nanomaterials have drawn a lot of interest in the material science community. However, extensive research is still needed to thoroughly analyze their safety profiles. Herein, we investigated the pulmonary impact and clearance of two-dimensional hexagonal boron nitride ( h -BN) nanosheets and boron nitride nanotubes (BNNTs) in mice. Animals were exposed by single oropharyngeal aspiration to h -BN or BNNTs. On days 1, 7, and 28, bronchoalveolar lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…To validate whether genotoxicity also occurs in bivalves after waterborne exposure ( in vivo ) experiments, we isolated hemocytes from clams exposed to NPs, and similar results were obtained (Figure S6e). Genotoxicity is a crucial end point in assessing the adverse effects of nanoparticles. , Prior research has demonstrated that nanoparticles can potentially impede DNA repair mechanisms, likely due to oxidative stress induced by the excessive accumulation of ROS. , DNA damage can lead to various consequences, including cell mutations, accelerated aging, and different forms of cell death such as necrosis, pyroptosis, and apoptosis. , Consequently, our in vitro cytotoxicity experiments reinforce the hypothesis that the NP exposure concentrations, extrapolated from the waterborne exposure ( in vivo ) experiments, can induce similar cytotoxic response patterns in the immune cells (hemocytes) of marine bivalves ( in vitro ).…”
Section: Resultssupporting
confidence: 74%
“…To validate whether genotoxicity also occurs in bivalves after waterborne exposure ( in vivo ) experiments, we isolated hemocytes from clams exposed to NPs, and similar results were obtained (Figure S6e). Genotoxicity is a crucial end point in assessing the adverse effects of nanoparticles. , Prior research has demonstrated that nanoparticles can potentially impede DNA repair mechanisms, likely due to oxidative stress induced by the excessive accumulation of ROS. , DNA damage can lead to various consequences, including cell mutations, accelerated aging, and different forms of cell death such as necrosis, pyroptosis, and apoptosis. , Consequently, our in vitro cytotoxicity experiments reinforce the hypothesis that the NP exposure concentrations, extrapolated from the waterborne exposure ( in vivo ) experiments, can induce similar cytotoxic response patterns in the immune cells (hemocytes) of marine bivalves ( in vitro ).…”
Section: Resultssupporting
confidence: 74%
“…On this basis, it is essential to evaluate the pharmacokinetics of 2D NMs to assess their metabolism and excretion [ 188 ]. Traditional pharmacokinetics relies on methods like inductively coupled plasma and Raman spectroscopy to analyze the concentration of 2D NMs over time in blood, organs, urine, and feces [ 189 ]. Nowadays, the in vivo tracking methods have been employed for real-time, non-invasive, and highly sensitive analysis of pharmacokinetics.…”
Section: Conclusion and Perspectivementioning
confidence: 99%